Inheritance of kid mortality in Jamunapari goats - ROY, R; SINGH, S K; SAXENA, V K (The Indian Journal of Animal Sciences, 2013)
Data recorded on posulatal mortality on 959 Jamunapari kids were utilized to study sire-wisemortalily patten in Jamunapari kids. ’lbree differen types of proportions: (A) number of kids died up to a particular age group v/s total number of kids born; (B) number of kids died within a particular age group v/s number of kids born and (C) number of kids died within a particular age group vis number of kids available in the beginning of the period. Differences among sire progeny groups were significant at all ages for proportions A and C and at 9-12 months for proportion B. The heritability estimate obtained by intrasire correlation method nmged form 0.13 to 0.305. Heritability values were lowest at 12 months. Therefore, for deciding the further use of sire in breeding programme heritability at 12 months may be given due consideration.